Mixing Analysis of Bamboo and Natural Iron Sand as a Magnetic Material - Helena Artasari Sihombing; Martha Riana; Syahrul Humaidi (IKIP Mataram, 2023)
This study aims to determine the magnetic properties of Fe3O4 synthesized from rope bamboo and natural iron sand. In this study, natural magnetic bio-char of bamboo and iron sand was synthesized by the co-precipitation method at a calcination temperature of 500oC. Then it was characterized through several tests, namely XRD and VSM. The results of the XRD test showed that the synthesis of natural bamboo + iron sand produced HKL peaks that were identical to Fe3O4 where these peaks were the peaks of magnetite and hematite. Magnetic properties were tested using VSM through a hysteresis curve with samples classified as soft magnets.